Profesionalizace vzdělávání učitelů pro primární školu - možnosti a meze - Anna Tomková; Vladimíra Spilková (Karolinum Press, 2019)
The aim of the review study is to reflect efforts to professionalize the education of primary school teachers in the Czech Republic. This means, on the basis of relevant theoretical and research resources, to assess both the strengths and the limits that have emerged in the realization of the professionally oriented preparation of future teachers in the wider context of international trends in this field. The introductory part of the contribution is devoted to changes in the concept of the profession, the changing demands on the roles and key competences of the teacher, on the quality of performance of the profession in connection with changes in school education. The trend towards professionalisation of teaching is reflected mainly in relation to primary school teaching. Specific characteristics of the primary school teacher's profession are presented as the basis for the concept of education of this category of teachers. The main focus of the paper is to reflect the key characteristics of professionalization of the primary school teachers' education and the possible ways to implement them. The possibilities and limits of these approaches will also be discussed on the basis of the comparison with selected foreign approaches.